On Fekete–Szegö Problems for Certain Subclasses of Analytic Functions Defined by Differential Operator Involving q-Ruscheweyh Operator. (8th January 2020) - Alsoboh, Abdullah; Darus, Maslina
Abstract : In this paper, we define a new derivative operator involving q -Ruscheweyh differential operator using convolution. Using this new operator, we introduce two new classes of analytic functions and obtain the Fekete–Szegö inequalities.